Prevalence and preventive measures of malaria among students of Imo State University, Owerri, Nigeria - Ogomaka, Ijeoma Ann (Orapuh Journal, 2020)
Introduction Episodes of malaria attack among students contribute immensely to high economic loss, poor academic performance due to absenteeism, and, occasionally, loss of life due to ignorance and negligence emanating from untreated malaria. Purpose The purpose of this study was to determine the prevalence and preventive measures of malaria among students of Imo State University, Owerri, Nigeria, to inform intervention initiatives. Materials & Methods A survey on the prevalence and preventive measures of malaria among students of Imo State University living off-campus was conducted between March and September 2019. A total of 618 students made up of 258 males and 360 females within the age range of 18 - 27+, who were randomly selected, participated in the study. Demographic and other information, including preventive measures in use, was obtained through responses to a well-structured questionnaire administered to them. Blood samples were collected by finger-pricking for the direct preparation of thick and thin blood smears. The blood films were prepared and stained with field stain A and B and examined with an x100 objective microscope for malaria parasites. Results Results obtained revealed that out of the 618 students examined, 78.3% had malaria parasites. Age group-related results showed that the age group, 23-26 years had the highest prevalence of malaria parasites (82.1%) while the least prevalence was observed among the age group of 27+ years (71.4%). Also, gender-related results revealed that males were more infected (90.00%) than females (69.4%). Data related to the preventive measures taken showed that participants that utilised window and door nets had the highest prevalence (90.6%) while those that utilised insecticide-treated bed nets (ITN) had the least prevalence (64.7%) of the infection. Results also indicated that those that lived close to refuse dumpsites had more infections (96.3%) than those that lived far from refuse dumpsites (58.8%). Further analyses of data revealed that a greater majority of the students were infected with malaria parasites (p<0.05) and the infection was significantly dependent on gender and preventive measures adopted (p<0.05) but independent of age groups (p>0.05). Conclusions There is an urgent need for education and enlightenment of the masses on the dangers of malaria infection and the proper employment of preventive measures. The government, also, needs to encourage general environmental sanitation to forestall further breeding of mosquitoes, while providing essential preventive amenities.